Prevalência de queixas de sintomas vestibulares em crianças - Said, Tuísa Souto (2012)
Vestibular function has assumed particular importance in recent years, especially in relation to the pediatric population, since the spatial perception, body balance, posture and motor coordination are indispensable at development of other functions, which are essentials to quality of life . Vestibular disorders are difficult to be recognized in children because they can not describe their symptoms accurately. However, it is important to deepen the investigation of complaints at childhood, dizziness especially, since some vestibular disorders detected only in adulthood have their origins in childhood. Studies indicate that a large number of children with balance disorders are diagnosed with nonspecific dizziness, which indicates there is need to improve the diagnostic accuracy of the professionals who treat these children. Objective: To investigate the prevalence of complaints of vestibular symptoms in children, as well as to investigate the association between dizziness and other symptoms indicative of possible vestibular disorders, further verifying any associations with other symptoms of motion sickness. Methods: exploratory, descriptive, prospective, and on a quantitative, conducted on a sample of 817 children. The questionnaire used was based on the model of Barbosa and El Malt (2007) and Niemensivu et al. (2006), which was adapted to suit the age group 6-12 years. Consisted of 17 objective questions that were answered by parents. Results: the most prevalent complaints directly related to vestibular disorders were: fumbling (30.5%), nausea / vomiting at riding a bus (19.3%), falls (13.7%), nausea / vomiting at riding a car (10.7%) and dizziness when standing up (9.1%). Among the complaints not directly related to vestibular disorders, the highlights were: headache (47.1%), distracted (46.1%), fear of the dark (43.9%), agitated (41.9%); and nightmares (29.4%). The complaint dizziness / vertigo was reported by 7.7%. When dizziness/vertigo was associated to others complaints directly related to vestibular disorders, it showed: nausea / vomiting at riding a bus (50%); fumbling (48.4%); unexplained nausea and nausea / vomiting at riding a car (29%); dizziness at standing up (27.9%); nausea / vomiting at playground (22%); and complaints not directly related to vestibular disorders showed: headache (76.2%); distracted (64.5%); fear of the dark and agitated (55.6%); unexplained fear or panic (49.2%); and nightmares (49.2%). The most expressive complaint associated with motion sickness was: distracted (75%); and among the variables pertaining to motion sickness, the highest proportion associated with dizziness / vertigo was nausea / vomiting at riding a bus (50%), which also had the highest prevalence referring to motion sickness (19.3%). Conclusion: of all complaints investigated and their associations, the highest rates were found between complaints not directly related to vestibular symptoms. The most prevalent complaint was headache, either alone (47.1%) and associated with dizziness / vertigo (76.2%). These results suggest the need for professionals directing more attention to complaints not traditionally related to vestibular disorders in their investigations